Cluster policy revisited in the digital age: by awareness and ownership to mission-oriented value creation - Götz, Marta (Studia z Polityki Publicznej, 2024)
This paper explores the interrelations between cluster (geographic concentration of interconnected entities) and Industry 4.0 (I4.0, business digital transformation) and the resulting consequences for cluster policy. Drawing on the case of Hamburg clusters, literature review and experts’ consultations, it aims to identify and formulate policy recommendations relevant to the cluster’s functioning in the digital transformation age. Whereas clusters may indeed nurture the implementation of Industry 4.0, the reverse impact of I4.0 on clusters can be diagnosed. Policy implications resulting from this co-evolution are discussed and recommendations for how to harness clusters as tools for advancing I.40 and to adjust cluster policy in digital time are formulated. Cluster policy revisited in the digital age should build upon raising awareness and ensuring ownership/legitimacy to enable mission-oriented joint value creation.